PENGARUH LIKUIDITAS, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA (Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Ananda, Riska; Ningsih, Endang Surasetyo (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this research to determine the effect of likuidity, ownership institusional, and firm size againts the earnings quality in manufacture companies listed on the Indonesia Stock Exchange in 2010-2014. The research type used in this research is hypothesis testing. by using purposive sampling method, there are 240 samples of manufacture companies data that become the object to be researched.The data type used is secondary data obtained from the financial statements and annual report, contained in the Indonesia Stock Exchange. The analysis used is multiple linear regression to test the hypothesis. The research results show that (1) likuidity has negative and significant influence toward earnings quality, (2) ownership institusional has positif and significant influence toward earnings quality, and (3) firm size has positif and significant influence toward earnings quality. Conclusion from this research that likuidity, ownership institusional, and firm size affect to earnings quality.Keywordsearnings quality, likuidity, ownership institusional, and firm size.